Centre-Periphery Analysis About the Hungarian Public Road System - Geza Toth (European Regional Science Association (ERSA), 2006)
Although the European Union prefers and supports mostly railways in terms of transport investments, the public road network – with a special regard to motorways – is rather underdeveloped in Hungary. Motorway construction has recovered after the change of regime. It is important not only to simply construct motorways but to work on the improvement of accessibility by validating the aspects of regional development, and thus the amounts invested have much more benefits. This view has been gaining ground mainly in the past period in Hungary. This paper analyses the accessibility conditions in 2005 by applying geographical information science methods, and examines if a favourable accessibility implies clearly a favourable level of development. The study also analyses which areas need new transport investments taking into consideration the circumstances of accessibility in 2005. By comparing the level of economic development and accessibility, the article seeks to answer at last how much favourable basis the present economic situation is for new public road investments.
Keywords: 330